Detection of Human Prion Seeding Activity in Formalin-Fixed Paraffin-Embedded Archival Tissues - Baranová, Soňa; Matěj, Radoslav; Safar, Jiri G; Holada, Karel (Neuropathology and applied neurobiology, 2025)
AIMS: Formalin-fixed paraffin-embedded (FFPE) samples, routinely used in neuropathology, represent an invaluable resource for studying rare diseases like transmissible spongiform encephalopathies (TSE). Despite fixation-induced protein cross-linking, prion seeding activity can be effectively detected using the seeding amplification assays. In this study, we employed the second-generation real-time quaking-induced conversion (RT-QuIC) assay to analyse and quantify human prion seeding activity in FFPE brain tissues. METHODS: FFPE frontal brain tissues were deparaffinised in xylene, followed by rehydration through descending concentrations of ethanol. The prion seeding activity in tissue homogenates was assessed by RT-QuIC assay utilising short recombinant hamster prion protein (rHaPrP90-231) as a substrate. RESULTS: A total of 60 samples, including 30 cases of confirmed TSE, comprising both sporadic and genetic forms, as well as 30 non-TSE controls, were analysed. Prion seeding activity has been detected in all TSE samples except one sCJD (VV2) and one GSS (P102L) case, corresponding to an assay sensitivity of 93.3%. Conversely, we did not detect any RT-QuIC positivity in the control group, resulting in 100% specificity. The mean 50% prion seeding dose of FFPE sporadic TSE samples was 107.8/g of brain tissue. CONCLUSION: Our study emphasises high sensitivity and specificity of RT-QuIC assay for prion detection in archival human FFPE brain tissues and demonstrates its diagnostic reliability comparable to other tissue types even after years of storage. The applicability of FFPE samples in RT-QuIC assays facilitates retrospective diagnostics and provides logistical advantages for sample preservation and transportation.
Keywords: Prion Proteins; SAA; Formaldehyde; real‐time quaking‐induced conversion assay; Brain; Prions; prion disease; seeding amplification assay; prion; Prion Diseases; priony; Paraffin Embedding; zalévání tkání do parafínu; RT‐QuIC; prionová bílkovina; formaldehyd; Animals; lidé; prionové nemoci; Humans; zvířata; fixace tkání; mozek; Tissue Fixation; formalin‐fixed paraffin‐embedded; FFPE